2011
DOI: 10.1111/j.1460-9568.2011.07631.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate released spontaneously from astrocytes sets the threshold for synaptic plasticity

Abstract: Astrocytes exhibit spontaneous calcium oscillations that could induce the release of glutamate as gliotransmitter in rat hippocampal slices. However, it is unknown whether this spontaneous release of astrocytic glutamate may contribute to determining the basal neurotransmitter release probability in central synapses. Using whole-cell recordings and Ca(2+) imaging, we investigated the effects of the spontaneous astrocytic activity on neurotransmission and synaptic plasticity at CA3-CA1 hippocampal synapses. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 74 publications
(198 reference statements)
9
118
0
4
Order By: Relevance
“…First, one might see excessive stimulation of perisynaptic and extrasynaptic metabotropic glutamate receptors (mGluRs). Overstimulation of presynaptic mGluR2 receptors has been shown to depress glutamate neurotransmission and compromise synaptic connectivity (99), consistent with the association of elevated anterior cingulate glutamate levels and reduced cingulate functional connectivity in major depression (100). Stress induced glutamate release also may enhance an NMDA/AMPA bias in signaling as stimulation of postsynaptic group I mGluRs enhances NMDA receptor signaling promotes long-term depression and internalization of AMPA receptors (101).…”
Section: Glutamate and The Neurobiology Of Depressionmentioning
confidence: 78%
“…First, one might see excessive stimulation of perisynaptic and extrasynaptic metabotropic glutamate receptors (mGluRs). Overstimulation of presynaptic mGluR2 receptors has been shown to depress glutamate neurotransmission and compromise synaptic connectivity (99), consistent with the association of elevated anterior cingulate glutamate levels and reduced cingulate functional connectivity in major depression (100). Stress induced glutamate release also may enhance an NMDA/AMPA bias in signaling as stimulation of postsynaptic group I mGluRs enhances NMDA receptor signaling promotes long-term depression and internalization of AMPA receptors (101).…”
Section: Glutamate and The Neurobiology Of Depressionmentioning
confidence: 78%
“…For example, a single gliotransmitter may exert multiple effects on the neuronal network depending on the receptor subtype and its subcellular membrane location. Indeed, glutamate released by astrocytes increases neuronal excitability by inducing slow inward currents (SICs) in excitatory neurons through activation of postsynaptic NMDA receptors (Parri et al, 2001; Angulo et al, 2004; Fellin et al, 2004; Perea and Araque, 2005; Navarrete and Araque, 2008; Shigetomi et al, 2008; Chen et al, 2012); but it also enhances synaptic transmission through activation of presynaptic metabotropic glutamate receptors (mGluRs) group I (Fiacco and McCarthy, 2004; Perea and Araque, 2007; Navarrete and Araque, 2010; Bonansco et al, 2011; Perea et al, 2014); and stimulates synaptic transmission by activation of presynaptic NMDA receptors in dentate granule cells (Jourdain et al, 2007). In addition, astrocytes release different gliotransmitters with different neuromodulatory effects.…”
Section: Brain Information Processing By Neuron–glia Networkmentioning
confidence: 99%
“…SICs trigger the synchronicity of neuronal activity [31,32] but their exact function and importance in the hippocampus is still unknown, and even questioned by some [21]. On the other hand mGluR5 receptor activation by astrocytes affects the release probability of the presynaptic terminals and consequently participates in synaptic plasticity [33,34]. Recently, experiments performed in vivo indicated that sensory stimulation and stimulations of the medial septal induced LTP at CA3-CA1 synapses [35].…”
Section: Synaptic Mechanisms and Memorymentioning
confidence: 98%